Debris flow monitoring in the acquabona watershed on the Dolomites (Italian alps) - Berti, M.; Genevois, R.; LaHusen, R.; Simoni, A.; Tecca, P.R. (Physics and chemistry of the earth. Part B, Hydrology, oceans and atmosphere, 2000)
In 1997 a field monitoring system was installed in Acquabona Creek in the Dolomites (Eastern Italian Alps) to observe the hydrologic conditions for debris flow occurrence and some dynamic properties of debris flow. The monitoring system consists of three remote stations: an upper one located at the head of a deeply-incised channel and two others located downstream. The system is equipped with sensors for measuring rainfall, pore pressures in the mobile channel bottom, ground vibrations, debris flow depth, total normal stress and fluid pore-pressure at the base of the flow. Two video cameras record events at the upper channel station and one video is installed at the lowermost station. During summer 1998, three debris flows (volumes from less than 1000 m3 up to 9000 m3) occurred at Acquabona. The following results were obtained from a preliminary analysis of the data: 1) All of the flows were triggered by rainfalls of less than 1 hour duration, with peak rainfall intensities ranging from 4.8 to 14.7 mm / 10 minute. 2) Debris flows initiated in several reaches of the channel, including the head of the talus slope. 3) The initial surges of the mature flows had a higher solid concentration and a lower velocity (up to 4 m/s) than succeeding, more dilute surges (more than 7 m/s). 4) Total normal stress and pore fluid pressures measured at the base of the flow. (mean depth about 1.1 m) were similar (about 15 kPa), indicating a completely liquefied flow. 5) Peak flows entrained debris at a rate of about 6 m 3/m of channel length and channel bed scouring was proportional to the local slope gradient and was still evident in the lower channel where the slope was 7°.